Families of austerity: benefit cutbacks and family stress in the UK - Mari, Gabriele; Keizer, Renske (Social forces, 2025)
Benefit cutbacks have been prominent after the Great Recession. The Family Economic Stress Model (FESM) theorizes how financial losses such as those spurred by cutbacks might adversely affect parental and child well-being. Yet, few links with policy have been established. We extend current knowledge by comprehensively assessing how benefits cutbacks may affect parents and their adolescent children. We rely on the first ten waves of the UK Household Longitudinal Study (2009–2019) and an event-study approach to examine the aftermath of an exceptional raft of benefit cutbacks. We find that mothers with lower incomes and single mothers accumulated losses equal to 20–30 percent of their household benefit income. Mothers could not fully compensate for such benefit income losses via their extra earnings, despite increased workforce participation. Financial worries, some forms of material hardship, and mental health worsened among mothers with lower incomes and single mothers exposed to cutbacks. Adolescent socio-emotional difficulties also increased in the period. We find little evidence, though, that cutbacks disrupted parenting. Parents thus display more agency than that accorded by the FESM. Nonetheless, findings point to deepening socioeconomic divides in financial and mental well-being, questioning the rationale for cutbacks.